Double ovarian tumour in the mare: Case report - Pinna, Aline E.; Okada, Carolina T. C. [UNESP]; Ferreira, Camila S. C.; Campos, Diego G.; Possidente, Karen S.; de Cássia C. L. Morais, Rita; Oliveira, Marcela; Salomão, Marcia Carolina; Hataka, Alexandre [UNESP] (Wiley, 2019)
Ovarian tumours in mares represent 2.5% to 6% of the most frequent neoplasms found in the equine species, with a higher chance of benignity. This study aims to describe a case of two different tumours found in the same ovary of a mare that presented clinical signs of suppressed oestrous cycle during 5 years. After unilateral ovariectomy, the ovary was sent to the histopathology examination which determined a mixed tumour of granulosa cell and leiomyosarcoma. After treatment, the mare returned to oestrus and got pregnant in the next season.
Keywords: anestrus; equine; histopathology; hormone; reproduction